Perlindungan Konsumen Terhadap Hak Keamanan Pangan di Lingkungan Sekolah Kabupaten Banyumas - Putri, Febi Listiyani Sunarto; Wardani, Susilo (UMPurwokerto Law Review, 2024)
Abstract There is some news that discusses consumer rights issues, including the right regarding food safety. Food safety is one of the rights that can be obtained by consumers, so it must be implemented by a business performer so that the food they sell is safe for consumption and does not cause health problems for those who consume it. It has been regulated in Article 4 letter (a) of Law Number 8 of 1999 concerning Consumer Protection which is supported by Article 111 paragraph (1) of Law Number 36 of 2009 conerning Health, Article 71 paragraph (1) of Law Number 18 of 2012 concerning Food, Article 1 paragraph (2) Regulation of the Minister of Health of the Republic of Indonesia Number 1096/Menkes/Per/VI/2011 concerning Jasaboga Sanitation Hygiene, and Article 1 paragraph (16) Government Regulation Number 86 of 2019 concerning Food Safety. This research aimed to identify and analyze the application of consumer rights regarding food safety in the Banyumas Regency school environment based on Article 4 letter (a) of the Consumer Protection Act and legal remidies that consumers can take if there is a violation of rights by business actors involving consumer health in the District of Banyumas. The research method used is normative juridical using secondary data sources. The results of this paper regarding the implementation of food safety right in the school environment in Banyumas Regency have not been fully implemented because it is still rare for food sellers who base themselves around schools to apply hygiene and health standards in the process of making the food they sell. Protection measures that consumers can take in the event of rights violations by business actors involving consumer health in the District Banyumas, namely by submitting complaints to some like the local public health center. Regarding dispute resolution, consumers can sue if there is a violation of rights by business actors that concerns consumer health, namely dispute resulation throught non-litigation channels and dispute resolution throught litigation channels. Keywords: consumer protection, food safety, school environment Â Abstrak Pada saat ini, sering terdengar adanya berita yang membahas tentang permasalahan hak konsumen, termasuk hak keamanan pangan. Keamanan pangan adalah salah satu hak yang dapat diperoleh konsumen, sehingga harus dilaksanakan oleh pelaku usaha agar pangan yang dijualnya aman untuk dikonsumsi serta tidak menimbulkan masalah kesehatan bagi yang mengonsumsinya. Keamanan ini telah diatur dalam Pasal 4 huruf (a) Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen yang didukung dengan Pasal 111 ayat (1) Undang-Undang Nomor 36 Tahun 2009 tentang Kesehatan, Pasal 71 ayat (1) Undang-Undang Nomor 18 Tahun 2012 tentang Pangan, Pasal 1 ayat (2) Peraturan Menteri Kesehatan Republik Indonesia Nomor 1096/Menkes/Per/VI/2011 tentang Higiene Sanitasi Jasaboga, serta Pasal 1 ayat (16) Peraturan Pemerintah Nomor 86 Tahun 2019 tentang Keamanan Pangan. Penulisan ini bertujuan untuk mengkaji dan menganalis penerapan hak konsumen atas keamanan pangan di lingkungan sekolah Kabupaten Banyumas berdasarkan Pasal 4 huruf (a) Undang-Undang Perlindungan Konsumen serta upaya hukum yang dapat konsumen lakukan apabila terjadi pelanggaran hak oleh pelaku usaha yang menyangkut kesehatan konsumen di Kabupaten Banyumas. Metode penelitian yang digunakan yaitu yuridis normatif dengan menggunakan sumber data sekunder. Hasil dari penulisan ini mengenai penerapan hak keamanan pangan di lingkungan sekolah Kabupaten Banyumas dalam kenyataannya masih belum dapat terlaksana sepenuhnya karena masih jarang penjual pangan yang memangkal di sekitar sekolah menerapkan standar kebersihan dan kesehatan dalam proses pembuatan pangan yang dijualnya. Upaya perlindungan yang dapat konsumen lakukan apabila terjadi pelanggaran hak oleh pelaku usaha yang menyangkut kesehatan konsumen di Kabupaten Banyumas yaitu dengan melakukan pengaduan ke beberapa pihak seperti puskesmas setempat, selain itu jalur non litigasi dan jalur litigasi dapat ditempuh apabila terjadi sengketa mengenai hal tersebut. Â Kata kunci: perlindungan konsumen, keamanan pangan, lingkungan sekolah